1977
DOI: 10.1042/bj1650447
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amphiphilic cationic drugs and inorganic cations on the activity of phosphatidate phosphohydrolase

Abstract: 1. Phosphatidate phosphohydrolase from the particle-free supernatant of rat liver was assayed by using emulsions of phosphatidate as substrate. 2. The inhibition of the phosphohydrolase by chlorpromazine was of a competitive type with respect to phosphatidate. The potency of various amphiphilic cationic drugs as inhibitors of this reaction was related to their partition coefficients into a phosphatidate emulsion. 3. The effect of chlorpromazine on the phosphohydrolase activity was complementary rather than ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 53 publications
(56 reference statements)
1
30
1
Order By: Relevance
“…3). This stimulation was much higher than was observed previously [18]. Substitution of EGTA for EDTA also stimulates PAP activity in the substrate that contained the higher concentrations of Ca2+, but it had no significant effect with the Ca2+-depleted substrate (Fig.…”
Section: Effects Of Chlorpromazine On Pap Activitycontrasting
confidence: 43%
See 2 more Smart Citations
“…3). This stimulation was much higher than was observed previously [18]. Substitution of EGTA for EDTA also stimulates PAP activity in the substrate that contained the higher concentrations of Ca2+, but it had no significant effect with the Ca2+-depleted substrate (Fig.…”
Section: Effects Of Chlorpromazine On Pap Activitycontrasting
confidence: 43%
“…Previous work had demonstrated that chlorpromazine could stimulate PAP activity and that it might replace the requirement for Mg2+ [18]. We therefore examined whether this applied under the present assay conditions with phosphatidate that contained the higher or lower concentrations ofCa2+.…”
Section: Effects Of Chlorpromazine On Pap Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of tightly bound Ca2+ in the phosphatidate used to prepare the emulsion is particularly inhibitory towards the soluble enzyme . Provided that Ca2+-free phosphatidate is used and its physical state is carefully controlled, then it can be efficiently degraded by the soluble enzyme (Hosaka et al, 1975;Bowley et al, 1977;Savolainen, 1977).…”
mentioning
confidence: 99%
“…Mn 2ϩ was equally effective compared with Mg 2ϩ for the binding of lipin-1 to PP-1c␥, whereas Ca 2ϩ was less effective. Lipin-1 and PP-1c both require Mg 2ϩ or Mn 2ϩ for their respective catalytic activities (23,39,40). Moreover, the interaction of lipin-1 with PP-1c␥ is mediated through a conserved HVRF motif on lipins, which closely resembles the canonical RVXF motif present on all PP-1c regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%